(untitled) (Indian Journal of Animal Production and Management, 2024)
Animal welfare encompasses the physical and psychological well-being of animals, ensuring they are healthy, comfortable, and free from stress. This involves providing adequate resources for their basic needs, such as food, water, shelter, and healthcare. Assessing animal welfare involves observing their behaviour and identifying any signs of distress or abnormal behaviour. Ethologists play a crucial role in studying and understanding animal behaviour patterns. While India has made progress in animal welfare legislation, challenges persist in enforcement and implementation. The Prevention of Cruelty to Animals Act of 1960, with subsequent amendments, provides a legal framework to protect animal welfare. However, challenges remain in ensuring its effective implementation. Other relevant regulations in India focus on transport, slaughterhouses, environmental protection, and marketing. To improve animal welfare in India, it is essential to strengthen existing laws, raise public awareness, and promote ethical practices in all aspects of animal care.